The Impact of Environmental and Anthropogenic Factors on the Migration of the Rural Arctic Population of Western Siberia - Elena Bogdanova; Konstantin Filant; Ekaterina Sukhova; Maria Zabolotnikova; Praskovia Filant; Dele Raheem; Olga Shaduyko; Sergei Andronov; Andrey Lobanov (Sustainability, 2022)
Environmental and anthropogenic factors represent challenges impacting the lifestyle and demographic rural population’s behaviour in the Russian Arctic that threaten its social and food security. We aim to explore (1) which key “push” factors are jeopardising social sustainability and increasing migration outflows in the Arctic rural communities of Western Siberia (2) and how the Siberian population’s sustainable development could be secured. The methodology and analysis were based on Lee’s theory of migration factors with the main focus on the “push” factors forcing people to migrate to other Arctic and non-Arctic territories. The primary sources included fieldwork data and interviews collected during expeditions to the Arctic zone of Western Siberia between 2000 and 2021. Both men and women confirmed the insignificant impact of environmental factors on their emigration plans. However, they signified social and personal motives related to low standards of living that threatened their social and food security. The rural Siberian population’s migration strategies could be re-evaluated only by increasing the physical availability of food products and developing the social infrastructure of the settlements as either “models of rural cities” or “service centres for nomadic and rural population”.